Design fabrication and testing of a solar cabinet drier for spices - ABDULLA HASHIM, P. A; Joby Joseph; Mohammed Shafi, M (Tavanur Kelappaji College of Agricultural Engineering and Technology, 1991)
project report
project report
Keywords: project report